Study of the migration of Fasciola hepatica juveniles across the intestinal barrier of the host by quantitative proteomics in an ex vivo model. - David Becerro-Recio; Judit Serrat; Marta López-García; Verónica Molina-Hernández; José Pérez-Arévalo; Álvaro Martínez-Moreno; Javier Sotillo; Fernando Simón; Javier González-Miguel; Mar Siles-Lucas (Public Library of Science (PLoS), 2022)
Fasciola hepatica is a trematode parasite that infects animals and humans causing fasciolosis, a worldwide-distributed disease responsible for important economic losses and health problems. This disease is of growing public health concern since parasite isolates resistant to the current treatment (triclabendazole) have increasingly been described. F. hepatica infects its vertebrate host after ingestion of the encysted parasite (metacercariae), which are found in the water or attached to plants. Upon ingestion, newly excysted juveniles of F. hepatica (FhNEJ) emerge in the intestinal lumen and cross the intestinal barrier, reach the peritoneum and migrate to the biliary ducts, where adult worms fully develop. Despite the efforts made to develop new therapeutic and preventive tools, to date, protection against F. hepatica obtained in different animal models is far from optimal. Early events of host-FhNEJ interactions are of paramount importance for the infection progress in fasciolosis, especially those occurring at the host-parasite interface. Nevertheless, studies of FhNEJ responses to the changing host environment encountered during migration across host tissues are still scarce. Here, we set-up an ex vivo model coupled with quantitative SWATH-MS proteomics to study early host-parasite interaction events in fasciolosis. After comparing tegument and somatic fractions from control parasites and FhNEJ that managed to cross a mouse intestinal section ex vivo, a set of parasite proteins whose expression was statistically different were found. These included upregulation of cathepsins L3 and L4, proteolytic inhibitor Fh serpin 2, and a number of molecules linked with nutrient uptake and metabolism, including histone H4, H2A and H2B, low density lipoprotein receptor, tetraspanin, fatty acid binding protein a and glutathione-S-transferase. Downregulated proteins in FhNEJ after gut passage were more numerous than the upregulated ones, and included the heath shock proteins HSP90 and alpha crystallin, amongst others. This study brings new insights into early host-parasite interactions in fasciolosis and sheds light on the proteomic changes in FhNEJ triggered upon excystment and intestinal wall crossing, which could serve to define new targets for the prevention and treatment of this widespread parasitic disease.